Effectiveness of the repair of unstabilised rammed earth with injection of mud grouts. (30th November 2016) - Silva, R.A.; Oliveira, D.V.; Schueremans, L.; Miranda, T.; Machado, J.
Highlights: The repair effectiveness of mud grouts is tested. The shear behaviour of rammed earth depends on binding, friction and interlocking. Mud grouts incorporating the same soil of the rammed earth perform better. Grout injection provides satisfactory strength recovery. Grout injection is incapable of recovering the initial shear stiffness. Abstract: The presence of cracks debilitates the structural performance of rammed earth. Grout injection is a repair solution put forward recently, where compatibility issues demand using mud grouts. Little is known on this topic, whereby an experimental program on the mechanical effectiveness of grout injection for repairing cracks in rammed earth was performed. Specimens tested under bending and diagonal compression were retested after repair with injection of mud grouts. Mud grouts incorporating the original soil of the rammed earth are shown to perform better and their injection achieves satisfactory shear strength recovery, but is less effective in recovering initial shear stiffness.